The history and petrography of Frobisher's "Gold ore" - Roy, Sharat Kumar, 1897-1962 (Chicago : Field Museum of Natural History, 1937)
"May 26, 1937." Caption title. Mode of access: Internet. Fieldiana series has been published as Geological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Geology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).